Pembelajaran PAI dan Pembinaan Keagamaan pada Anak Tunalaras di SLB Bina Siwi - Difa'ul Husna; Agung Budi Putranto; Khalida Lutfiah Munir; Salim Ibrahim Bin Kadim; Iffatur Rohmah (Peneliti.net, 2023)
The research aims to find out how PAI learning and religious coaching are for mentally retarded students. The method used in the study of literature and observation. This research was conducted at a school with special needs, namely at SLB Bina Siwi, Bantul Yogyakarta. Children with disabilities is a term for children who experience obstacles in controlling emotions and social control. This research was conducted at one of the ABK schools, namely at Bina Siwi SLB, Bantul, Yogyakarta. Students with disabilities have the opportunity to develop according to their developmental tasks. There are many factors that arise from students with disabilities, both internal and external which cause them to do things that deviate, have an inability to adapt, commit aggression and chaos and disturb other people and the environment. The results of this study are that the habituation model for PAI learning at Bina Siwi Special School is to get used to greeting as soon as you arrive at school until you come home from school. And for religious development is by getting used to praying dhuha and midday prayers for students.